2016
DOI: 10.3349/ymj.2016.57.2.393
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis on the Effects of House Dust Mite Specific Immunotherapy for More Than 3 Years in Atopic Dermatitis

Abstract: PurposeIn extrinsic atopic dermatitis (AD), house dust mites (HDM) play a role in eliciting or aggravating allergic lesions. The nature of skin inflammation in AD has raised a growing interest in allergen-specific immunotherapy (SIT). Thus, we assessed clinical improvement and laboratory parameters for evaluation of the benefit of long-term SIT.Materials and MethodsA total of 217 AD patients who were treated with SIT for at least 3 years were retrospectively assessed, by using their investigator global assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 26 publications
3
23
0
4
Order By: Relevance
“…Previous studies on the analysis of predictive factors for the clinical efficacy of SCIT in patients with allergic rhinitis and allergic asthma have suggested that levels of total serum IgE or allergen-specific IgE could be used as a predictive marker for clinical efficacy of SCIT 22. In this study, we could not find any differences in baseline laboratory parameters between patients with AD showing a favorable clinical response to SCIT and the patients with AD showing no significant clinical response to SCIT, similar to a previous study 19. Further studies to identify predictive biomarker for clinical efficacy of SCIT in patients with AD are needed 23…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies on the analysis of predictive factors for the clinical efficacy of SCIT in patients with allergic rhinitis and allergic asthma have suggested that levels of total serum IgE or allergen-specific IgE could be used as a predictive marker for clinical efficacy of SCIT 22. In this study, we could not find any differences in baseline laboratory parameters between patients with AD showing a favorable clinical response to SCIT and the patients with AD showing no significant clinical response to SCIT, similar to a previous study 19. Further studies to identify predictive biomarker for clinical efficacy of SCIT in patients with AD are needed 23…”
Section: Discussionsupporting
confidence: 90%
“…In patients with allergic rhinitis, patients showing a favorable clinical response to SCIT had a significantly shorter duration of symptom than patients showing no significant clinical response to SCIT in a previous study 18. In patients with AD, clinical outcomes for SCIT were better in patients younger than 12 years of age than patients older than 12 years in a previous study 19. These results suggest that early initiation of SCIT after onset of symptoms might provide a favorable clinical outcome in patients with severe AD sensitized to HDM.…”
Section: Discussionmentioning
confidence: 56%
“…Sensitization to house dust mites was confirmed in these patients, and allergen-specific immunotherapy was proved to be effective, with 92.7% of the patients showing improvement of pruritus and 45% of the patients achieving remission. Only 16% of the patients showed either minimal improvement or no change 4447. Its safety was also proved, with only 0.1% of systemic adverse effects, such as flu-like symptoms, observed in our institution.…”
Section: Discussionmentioning
confidence: 52%
“…SIT is well established as the modality which has been proven in controlled prospective studies and is currently used in the management of allergic rhinitis, allergic asthma, and venom allergy . In atopic dermatitis (AD), SIT has been recently supported by a randomized controlled trial and meta‐analysis, especially in patients sensitized with house dust mite allergen . The mechanisms of how SIT ameliorates allergic reactions are not completely understood, but peripheral T‐cell tolerance is thought to play an important role .…”
Section: Introductionmentioning
confidence: 99%